Pelatihan dan Pendampingan Penciptaan Lagu Anak Tematik Bagi Guru Sekolah Dasar di Magetan - Mariati, Pance; Nafiah, Nafiah; Hartatik, Sri; Rulyansah, Afib (Indonesia Berdaya, 2022)
Learning during the COVID-19 pandemic requires all educators to be more creative and innovative in packaging subject matter. The subject matter presented is not only interesting but also must be able to maximize the competencies possessed by students. Therefore, learning materials must be made very pleasant and easy to understand. The purpose of this Community Service (PPM) activity is to provide elementary school teachers with skills and insight in creating simple and interesting children's songs according to the theme of the lesson in elementary school, so that students can be more interested and easily understand the material presented by the teacher. The method used in this activity is training and mentoring which is carried out online with the target subject of 73 elementary school teachers in Magetan. The stages of training activities include working on pre-test questions, explaining song creation material, practicing individual children's song creations, assisting in creating children's songs via WhatsApp, Telegram groups and Google Drive, presenting the results of song creation followed by evaluation of the next activity working on post-test questions. The result of the implementation of training and mentoring activities is that elementary school teachers can better understand how to make children's songs according to simple, easy and interesting lesson themes. This can be seen from the results of making song lyrics that are in accordance with the theme of the lesson, making good tones that are created by themselves or using existing tones and being able to sing songs that have been created. The conclusion is that the training and mentoring activities for the creation of thematic children's songs have been carried out well and provide benefits to elementary school teachers. It is hoped that similar activities can continue to be carried out in order to increase teacher creativity.